Water balance, flow duration and frequency in a small experimental watershed in Kinabalu Park, Sabah - Kanehiro Kiyatama; Kochiro Kuraji; Mie Gomyo (Penerbit Universiti Malaysia Sabah, 2011)
We examined the water balance and hydrological characteristics of tropical montane forests in Kinabalu Park.